(3ebGdI GdEScfOQ GdEaQhOjSi aj EHWGd bhd ef bGd (B: (3Efg dGjchf TF EdG ef TF hEKHGJ Cf cd TF EfeG jchf dGef TFs - (3GdEScfOQ GdEaQhOjSis
(3ChdgG (B:s
(3bGd (B: (3Ef fGSkG ef GdChdjf bGdhG (B: (3Efg dGjecf Cf jchf TF EdG ef TF s
(3BNQgG (B:s
(3Ch bO jbOQ Cf GdNeS GdCLQGe GdJi ef GdCQV Edi Gdadc gPG BNQ eG hLO ef gPg GdebGdI , hGdMeO ddg cKjQkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(798/7) s
Keywords: (3GdadSaI hGdefWbs